The Lost Library of Jacques Philippe d'Orville: The Missing Manuscripts and Annotated Books of the D'Orville Collection. - Vioque, Guillermo Galán (Quaerendo, 2017)
The present article is an investigation of the manuscripts and annotated books formerly belonging to the Dutch scholar Jacques Philippe d'Orville (1696-1751) which did not enter the Bodleian Library along with the rest of his library. Evidence is provided that disproves the commonly accepted assertion that d'Orville's library, which today is known as the D'Orville collection, entered the Bodleian almost intact.